Respon Pertumbuhan dan Kualitas Hasil Beberapa Varietas Tomat pada Berbagai Frekuensi Penyiraman - Cicilia Tri Kusumastuti; Ardiyanta Ardiyanta (Fakultas Pertanian, Universitas Timor, 2019)
The Research of the growth response and the resulting quality of the several tomatoes varieties on various watering periods was conducted on May-August 2016 in the Greenhouse, Agriculture Faculty of Universityof PGRI Yogyakarta. This research was used Randomized Complete Block Design (RCBD) and has two factors in the research. The first factor is the various watering periods (every day, 2 days, 4 days and 6 days) and the second factor is varieties of tomato (Timothy, Servo, and Betavila). The parameters of the observed were plant height, leaves of chlorophyll, biomass, fruit set, fruit number per plant, fruit weight per plant, the diameter of fruit, fruit coefficient, fruit ripening, and vitamin C. The results show that no interaction between various watering periods and varieties of tomato. Watering period every day has a significant effect of plant height, leaves of chlorophyll, biomass, fruit set, fruit number per plant, fruit weight per plant and vitamin C. Betavila varieties showing the best result of the other varieties of tomato.